Combining revealed and stated preference methods to assess the private value of agrobiodiversity in Hungarian home gardens - Birol, Ekin; Kontoleon, Andreas; Smale, Melinda (International Food Policy Research Institute, 2006)
Hungarian home gardens are small-scale farms managed by farm households using traditional management practices and family labor. They generate private benefits for farmers by enhancing diet quality and providing food when costs of transacting in local markets are high. Home gardens also generate public benefits for society by supporting long-term productivity advances in agriculture. In this paper, we estimate the private value to farmers of agrobiodiversity in home gardens. Building on the approach presented in EPTD Discussion Paper 117 (2004), we combine a stated preference approach (a choice experiment model) and a revealed preference approach (a discrete-choice, farm household model). Both models are based on random utility theory. To combine the models, primary data were collected from the same 239 farm households in three regions of Hungary. Combining approaches leads to a more efficient and robust estimation of the private value of agrobiodiversity in home gardens. Findings can be used to identify those farming communities, which would benefit most from agri-environmental schemes that support agrobiodiversity maintenance, at least public cost.